Pendidikan Evidence-Based Practice Melalui Mentoring Program oleh Perawat di Rumah Sakit: A Literature Review - Saldy Yusuf; Kadek Ayu Erika; Kusrini Kadar; Juhelnita Juhelnita; Wahyu Hidayat (Jurnal Keperawatan Muhammadiyah, 2019)
Background: Coaching or training by mentors in the literature search process and utilization of research results can foster a positive culture both in the unit and in the organization. Objective: to identify the effectiveness of EBP education through a mentoring program by nurses in hospitals. Methods: Search articles using keywords to find the results of research that discusses the education of EBP nurses by hospital mentors in three journal portals indexed by PubMed, Wiley, and ScienceDirect, then using the Critical Appraisal Skills Program (CASP) Randomized control trial as a tool for extracting obtained. Results: The EBP education program carried out is able to improve the knowledge and skills, attitudes,and beliefs of nurses to searching information and integrate into evidence-based practice. Conclusion: EBP education through a mentoring program can improve the implementation of evidence-based practices in hospitals Future research needs to focus on longitudinal studies to evaluate the long-term effect of EBP education programs on organizational culture